The maid : [large type] a novel - Prose, Nita (Random House Large Print, 2022)
"Molly Dunn is not like everyone else. She struggles with social skills and interprets people literally. Since her Gran died a few months ago, twenty-five-year-old Molly has had to navigate life's complexities all by herself. No matter--she throws herself with gusto into her work as a hotel maid. Her unique character, along with her obsessive love of cleaning and proper etiquette, make her an ideal fit for the job. But Molly's orderly life is turned on its head the day she enters the suite of the infamous and wealthy Charles Black, only to find it in a state of disarray and Mr. Black himself very dead in his bed. Before she knows what's happening, Molly's odd demeanor has the police targeting her as their lead suspect and she finds herself in a web of subtext and nuance she has no idea how to untangle. Fortunately for Molly, a medley of friends she didn't realize she had refuses to let her be charged with murder--but will they be able to discover the real killer before it's too late?"--